How do first-year engineering students experience ambiguity in engineering design problems: The development of a self-report instrument - Dringenberg, Emily; Wertz, R. E. H. (My University, 2017)
Design is widely recognized as a keystone of engineering practice. Within the context of engineering education, design has been categorized as a type of ill-structured problem solving that is crucial for engineering students to engage with. Improving undergraduate engineering education requires a better understanding of the ways in which students experience ill-structured problems in the form of engineering design. With special attention to the experiences of first-year engineering students, prior exploratory work identified two critical thresholds that distinguished students' ways of experiencing design as less or more comprehensive: accepting ambiguity and recognizing the value of multiple perspectives. The goal of current (work-in-progress) research is to develop and pilot a self-report instrument to assess students' relation to these two thresholds at the completion of an ill-structured design project within the context of undergraduate engineering education. The specific research questions addressed in this study are 1) if the piloted self-report instrument can be used to identify discrete constructs, and 2) how these constructs align with prior qualitative research findings. The objective of this study was addressed using a quantitative exploratory research design. Items for the self-report Likert-scaled instrument were designed to distinguish student experience that either accept or reject the presence of ambiguity and the value of multiple perspectives. The instrument was disseminated to a total of 214 first-year engineering students. Exploratory factor analysis was used to identify the constructs that emerge from the self-report data, and these constructs were checked for alignment with the previously identified thresholds. The results of this investigation will be used to help advance progress towards an easily administered instrument able to assist engineering educators with the identification of students in need of intervention or explicit instruction related to critical aspects of learning engineering design. The instrument could also be used to track student growth over time, and, with further development, to provide evidence for ABET student outcomes. © American Society for Engineering Education, 2016.
Citation: Dringenberg, E., & Wertz, R. E. H. (2016). How do first-year engineering students experience ambiguity in engineering design problems: The development of a self-report instrument.